Evaluasi Implementasi Peraturan Daerah Nomor 03 Tahun 2018 Tentang Pajak Parkir Di Kota Pekanbaru - Elsa Monika; Nur Laila Meilani (Pusat Riset dan Inovasi Nasional, 2023)
Regional Original Revenue (PAD) is a source of regional revenue that comes from several regional revenues and one of them is obtained from local tax revenues, one type of which is parking tax. In order to regulate parking tax management, Pekanbaru City Regional Regulation Number 03 of 2018 concerning Parking Tax was issued, which is implemented by the Pekanbaru City BAPENDA. In the Pekanbaru City Regional Regulation Number 2 of 2011 concerning Parking Tax in article 1 point 8, it states that